Aplicação de sal micronizado e ultrassom como estratégia para reduzir sódio em produtos cárneos emulsionados - Rosa, Jordana Lima da (2022)
In this study, the combination of high-power ultrasound (HPU), micronized salt (MS) and low-level of KCl was used as a strategy to reduce the sodium content of emulsified sausages. Thus, sausages with 50% NaCl reduction were produced with regular salt (RS) or MS and with the addition of 0.5% KCl. The samples were sonicated for 27 min in an ultrasonic bath (normal mode, 25 kHz, 60% amplitude, 20 ºC) immediately after embedding. The applied sodium reformulation strategy was effective to compensate for defects in emulsion stability and texture profile caused by NaCl reduction. In addition, the combination of HPU, MS and KCl also did not cause major impacts on the evolution of the pH, Eh and TBARS values of the samples during storage (21 days at 4 ºC). Besides, the use of MS and KCl made it possible to reduce the NaCl content by 50% (< 42% Na; Na/K ratio: 1.2-1.3) of the samples without affecting their salty taste, and this attribute was enhanced by the HPU.